HEADS OF DEPARTMENT ADMINISTRATIVE LAW STRATEGIES OF MANAGING SCHOOLS IN TIMES OF CRISIS - Mahlangu, Vimbi Petrus (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
The purpose of this article is to provide schools with the necessary knowledge and skills to manage sustained crises in schools. The role of heads of department (HODs) in administering schools during times of crisis is covered in this article. The Covid-19 crisis has brought to light a new chance to explore the role of HODs, the stakeholders they represent, and how they could progress toward a larger understanding and better response to critical school concerns. As a result, the author's goal in this article is to find out "How should HODs exercise their powers in crisis management?" The author emphasizes the significance of flexibility and organizational creativity in times of crisis based on this investigation. The author also discusses how HODs can bridge the gap between school administrators and teachers, school crisis management and resolution, knowledge of technology information, and communication, virtual learning, communication, crisis management strategies, and how principals can support HODs when the next crisis is right around the corner. The Corona Virus (Covid-19) epidemic created fear and vulnerability among people and school personnel and students, particularly in educational systems.